Analisis Praktik Berkelanjutan dalam Peternakan Domba: Studi Kasus pada 72 Al-Fath Farm - puspita, angela candra; Heikal, Jerry (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
This research was conducted with the main aim of analyzing sustainable practices in sheep farming, focusing on a case study conducted at 72 Al-Fath Farm. A case study approach was used as a research method to dig deeper into the practices implemented in the context of sustainable sheep farming. The grounded theory method was chosen as the research framework, allowing the researcher to gain an in-depth understanding of various aspects of sustainable practices in sheep farming, including operational management, marketing strategies, and the implementation of environmentally friendly practices. The data collection process was carried out through in-depth interviews with owners and breeders at 72 Al-Fath Farm. The qualitative data obtained from the interviews was then analyzed using the grounded theory method. The results of the first analysis produced 61 codings, where the researcher gave labels or codes to relevant pieces of information from the interview results. Next, the second analysis grouped the codes into 8 categories that reflected the concepts that emerged from the data. Finally, the third analysis identified 3 general themes that reflect the essence of the findings, providing a broader understanding of sustainable practices in the sheep farming context. The results of this research show that 72 Al-Fath Farm implements sustainable practice patterns in various operational aspects. These findings provide valuable insight into the challenges and opportunities in implementing these practices, as well as their potential positive impact on the sustainability of sheep farming. It is hoped that the findings of this research will provide an important contribution to livestock practitioners, researchers, and decision makers in their efforts to improve sustainability in sheep farming. With a deeper understanding of sustainable practices, it is hoped that more effective strategies and policies can be developed to support sustainable sheep farming in the future